Validation and Comparison of Four Mortality Prediction Models in a Geriatric Ward in China - Li Y; Liu X; Kang L; Li J (Clinical Interventions in Aging, 2023)
Yuanyuan Li, Xiaohong Liu,* Lin Kang,* Jiaojiao Li Department of Geriatrics, Peking Union Medical College, Chinese Academy of Medical Sciences, Peking Union Medical College Hospital, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaohong Liu; Lin Kang, Department of Geriatrics, Peking Union Medical College, Chinese Academy of Medical Sciences, Peking Union Medical College Hospital, Beijing, People’s Republic of China, Email xhliu41@sina.com; kangl@pumch.cnPurpose: The efficacy of mortality risk prediction models among older patients in China remains uncertain. We aimed to validate and compare the performances of the Walter Index, Geriatric Prognostic Index (GPI), Charlson Comorbidity Index (CCI), and FRAIL Scale in predicting 1-year all-cause mortality post-discharge in geriatric inpatients in China.Patients and Methods: This study was conducted at a geriatric ward of a tertiary Hospital in Beijing, including patients aged 70 years or older with a documented comprehensive geriatric assessment, discharged between January 1, 2016, and December 31, 2021. Patients with a hospital stay ≤ 24 h or > 60 days were excluded. All-cause mortality data within one year of discharge were collected from medical files and telephone interviews between August 2022 and February 2023. Multiple imputation, Logistic regression analysis, Brier scores, C-statistics, Hosmer-Lemeshow goodness-of-fit-test, and calibration plots were employed for statistical analysis.Results: We included 832 patients with a median (interquartile range) age of 77 (74– 82) years. One-hundred patients (12.0%) died within one year. After adjusting for covariates—marital status, social support, cigarette use, length of stay, number of medications, hemoglobin levels, handgrip strength, and Short Physical Performance Battery—CCI scores of 3– 4 and > 4, and increased Walter Index, GPI, and FRAIL Scale scores were significantly associated with 1-year mortality risk. The Brier scores varied from 0.07 (Walter Index) to 0.10 (FRAIL Scale). The C-statistic ranged from 0.74 (95% confidence interval, 0.69– 0.78) for FRAIL Scale to 0.88 (95% confidence interval, 0.84– 0.91) for the Walter Index. Calibration curves showed that the Walter Index, GPI, and FRAIL Scale were well calibrated, while the CCI was poor.Conclusion: Combining the Brier score, discrimination and calibration, the Walter Index was confirmed for the first time to be the best model to predict the 1-year mortality risk of geriatric inpatients in China among the four models.Keywords: aged, care for older adults, comprehensive geriatric assessment, frail, prediction models